2020
DOI: 10.1002/jat.4126
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofNigella sativaextract against H2O2‐induced cell death through the inhibition of DNA damage and cell cycle arrest in human umbilical vein endothelial cells (HUVECs)

Abstract: Oxidative stress is known to induce cytotoxicity and apoptosis in endothelial cells and indorse development of atherosclerosis. The aim of this research was to assess the cytoprotective effects of ethanolic extract of Nigella sativa (NSE) against H2O2‐induced cell death in human umbilical vein endothelial cells (HUVECs) and also study the probable mechanisms through which NSE exhibited cyto‐protection. The cytotoxicity was measured by exposing the HUVECs with NSE (10–200 μg/ml) and H2O2 (25–1000 μM) for 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
(79 reference statements)
2
3
0
Order By: Relevance
“…In addition to the mentioned effects, anti-hemolytic activity has also been noticed [ 31 ] ( Table 1 ). These results are in accordance with those obtained in the study of Farshori et al, 2021 [ 32 ] where the pretreatment of human umbilical vein endothelial cells (HUVEC) with different doses of the ethanolic extract of the NS seeds protected the cells from the negative effect of the H 2 O 2 which confirms the antioxidant effect of the plant. The radiations have an enormous interactive capacity with human tissue and can cause free radical generation by radiolysis of water molecules which induce damage at the level of the DNA and cell death.…”
Section: Pharmacological Properties Of Nigella Sativasupporting
confidence: 92%
“…In addition to the mentioned effects, anti-hemolytic activity has also been noticed [ 31 ] ( Table 1 ). These results are in accordance with those obtained in the study of Farshori et al, 2021 [ 32 ] where the pretreatment of human umbilical vein endothelial cells (HUVEC) with different doses of the ethanolic extract of the NS seeds protected the cells from the negative effect of the H 2 O 2 which confirms the antioxidant effect of the plant. The radiations have an enormous interactive capacity with human tissue and can cause free radical generation by radiolysis of water molecules which induce damage at the level of the DNA and cell death.…”
Section: Pharmacological Properties Of Nigella Sativasupporting
confidence: 92%
“…A dose‐dependent decrease in HaCaT cell viability was previously reported in HaCaT cells exposed to H 2 O 2 (100–500 μM) for 12 h, by MTT assay, with a 50% cell mortality at the concentration of 350 μM H 2 O 2 (Zhang et al, 2020), whereas a survival rate of about 60% was reported by Park et al (2020) for HaCaT cells exposed to 500 μM H 2 O 2 for 24 h. In our study, the H 2 O 2 cytotoxic effect was also confirmed by microscopic observation, which allowed to assess the presence of apoptotic features and decreased cell density. Similar morphological alterations were observed in other cell types exposed to H 2 O 2 ‐damage, such as human umbilical vein endothelial cells, neuroblastoma cell line SK‐N‐MC, and HepG2 cells (Bayati et al, 2011; Farshori et al, 2021; Liao et al, 2022). Pre‐treatment with arzanol preserved HaCaT cells from H 2 O 2 cytotoxicity, and significant greater cell viability was observed in arzanol‐treated cells in comparison with those no‐treated exposed to the highest concentrations of oxidants.…”
Section: Discussionsupporting
confidence: 66%
“…A dose-dependent decrease in HaCaT cell viability was previously reported in HaCaT cells exposed to H 2 O 2 (100-500 μM) for 12 h, by MTT assay, with a 50% cell mortality at the concentration of 350 μM H 2 O 2 (Zhang et al, 2020), whereas a survival rate of about 60% was reported by Park et al (2020) for HaCaT cells exposed to 500 μM H 2 O 2 for 24 h. In our study, the H 2 O 2 cytotoxic effect was also confirmed by microscopic observation, which allowed to assess the presence of apoptotic features and decreased cell density. Similar (Bayati et al, 2011;Farshori et al, 2021;Liao et al, 2022 (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…It is well established that oxidation of low‐density lipoprotein (LDL) particles contributes to the formation of oxidized LDL, which can be cytotoxic and cause the initial disruption of endothelial cells and subsequent injury to vascular walls (Siti et al, 2015 ; Tesfamariam & DeFelice, 2007 ). Previous studies showed several natural active substances had protective effect on vascular endothelial cells (Farshori et al, 2021 ; Guo et al, 2021 ; Liao et al, 2021 ). Numerous studies have shown that antioxidants originating from plants, such as vitamins E and C, tocopherols, β‐carotene, and polyphenols, may be protective against cardiovascular disorders (Siti et al, 2015 ; Wang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 96%
“…It is well established that oxidation of low-density lipoprotein (LDL) particles contributes to the formation of oxidized LDL, which can be cytotoxic and cause the initial disruption of endothelial cells and subsequent injury to vascular walls (Siti et al, 2015;Tesfamariam & DeFelice, 2007). Previous studies showed several natural active substances had protective effect on vascular endothelial cells (Farshori et al, 2021;Guo et al, 2021;Liao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%